Antimicrobial activities of Nardostachys jatamansi extract against multidrug resistant bacterial species - Piyali Karmakar; Sayan Paul; Bhaskar Narayan Chaudhuri; Partha Guchhait; Satadal Das (German Journal of Pharmaceuticals and Biomaterials, 2022)
At present, multidrug resistant (MDR) bacteria have become widespread worldwide, leading to high morbidity and mortality rates in bacterial infections. Again, as there is practically no new antimicrobial agent in the pipeline, this will create a threat to humanity for their survival. In this study, we explored the possible antimicrobial action of ethanolic extract of a typical plant of West Bengal, Nardostachys jatamansi, against MDR and American Type Culture Collection (ATCC) strain bacteria. Antimicrobial activities of Nardostachys jatamansi ethanol extract were studied by disc diffusion technique, and then minimum inhibitory concentration (MIC) determination was done by serial dilution in Mueller Hinton broth. Ethanolic extract of Nardostachys jatamansi showed antimicrobial activities with MIC varied between 2.77- 5.82 mg/mL in both MDR and ATCC bacteria. Ethanolic extract of Nardostachys jatamansi is an effective antimicrobial agent on MDR bacteria and may help save the lives of many critically ill patients.